White death : a novel from the NUMA files - Cussler, Clive (Cussler, Clive. NUMA files., 2003)
Hailed as a hero for the new millennium, Austin is the leader of NUMA(r)'s Special Assignments Team-and the threat before him now is definitely special. A confrontation between a radical environmentalist group and a Danish cruiser has forced Austin and colleague Joe Zavala to come to the rescue of a shipful of trapped men; but when the two of them investigate further, they discover that something far more sinister is at work. A shadowy multinational corporation is attempting to wrest control of the very seas themselves-no matter what havoc results-and is killing anyone who attempts to stop them. When Austin's boat blows up and he just barely survives, it seems certain he is the next in line to die-but he cannot stop now. For the environmental disaster has already begun, and only he and NUMA(r) stand in the way. . . .